Short segment Barrett's esophagus and distal gastric intestinal metaplasia - Dietz,Judite (2006)
BACKGROUND: Short segment Barrett's esophagus is defined by the presence of <3 cm of columnar-appearing mucosa in the distal esophagus with intestinal metaplasia on histophatological examination. Barrett's esophagus is a risk factor to develop adenocarcinoma of the esophagus. While Barrett's esophagus develops as a result of chronic gastroesophageal reflux disease, intestinal metaplasia in the gastric cardia is a consequence of chronic Helicobacter pylori infection and is associated with distal gastric intestinal metaplasia. It can be difficult to determine whether short-segment columnar epithelium with intestinal metaplasia are lining the esophagus (a condition called short segment Barrett's esophagus) or the proximal stomach (a condition called intestinal metaplasia of the gastric cardia). AIMS: To study the association of short segment Barrett's esophagus (length <3 cm) with gastric intestinal metaplasia (antrum or body) and infection by H. pylori. PATIENTS AND METHODS: Eight-nine patients with short segment columnar-appearing mucosa in the esophagus, length <3 cm, were studied. Symptoms of gastroesophageal reflux disease were recorded. Biopsies were obtained immediately below the squamous-columnar lining, from gastric antrum and gastric corpus for investigation of intestinal metaplasia and H. pylori. RESULTS: Forty-two from 89 (47.2%) patients were diagnosed with esophageal intestinal metaplasia by histopathology. The mean-age was significantly higher in the group with esophageal intestinal metaplasia. The two groups were similar in terms of gender (male: female), gastroesophageal reflux disease symptoms and H. pylori infection. Gastric intestinal metaplasia (antrum or body) was diagnosed in 21 from 42 (50.0%) patients in the group with esophageal intestinal metaplasia and 7 from 47 (14.9%) patients in the group with esophageal columnar appearing mucosa but without intestinal metaplasia. CONCLUSION: Intestinal metaplasia is a frequent finding in patients with <3 cm of columnar-appearing mucosa in the distal esophagus. In the present study, short segment intestinal metaplasia in the esophagus is associated with distal gastric intestinal metaplasia. Gastroesophageal reflux disease symptoms and H. pylori infection did not differ among the two groups studied.